Social Influence, Perception of Convenience, Perception of Usefulness, Trust and Security on Repurchase Decisions on The Pospay Application - Andriani, Puput Herlinda; Krisnawati, Wenti (Dinasti International Journal of Management Science, 2026)
This study aims to analyze the social influences, Perceive Esay Of Use, Perceive Usefulness, Trust, And Security on Purchase Intention to Pospay Application Study Case Peoples at Jember. The research adopts a descriptive quantitative approach designed to systematically and measurably describe the characteristics of the studied population or phenomenon. Data obtained through this approach were analyzed using statistical techniques. The results indicate that Social influence has a positive and significant effect on repurchase decisions, perceived ease of use has a positive and significant effect on repurchase decisions, perceived usefulness has a positive and significant effect on repurchase decisions, trust has a positive and significant effect on repurchase decisions, and security has a positive and significant effect on repurchase decisions